2002
DOI: 10.1097/00003246-200203000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heparin and lisofylline on pulmonary function after smoke inhalation injury in an ovine model*

Abstract: Treatment with heparin alone did not attenuate pulmonary dysfunction after severe smoke injury. Combined treatment with nebulized heparin and systemic lisofylline had beneficial effects on pulmonary function in association with a decrease in blood flow to poorly ventilated areas and less lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…In fact cholesterols, elevated to the levels measured in the airways of subjects with ALI (14,44), more prominently inhibit the surface tension lowering effects of surfactant in vitro than do serum proteins (21), a disparity that could also apply in vivo. With this in mind, it is curious to note that most studies reporting improved lung function with the use of fibrinolytic agents in ALI have focused predominantly on ventilationperfusion matching and oxygenation (2,16,50,57), with limited reporting on changes in lung mechanical function. The one study reporting a reduction in peak airway pressures following aerosolized tPA used a sheep model of burn and smoke inhalation injury (16), a model characterized by extensive obstruction of large and small airways with fibrinous debris (16).…”
Section: Discussionmentioning
confidence: 99%
“…In fact cholesterols, elevated to the levels measured in the airways of subjects with ALI (14,44), more prominently inhibit the surface tension lowering effects of surfactant in vitro than do serum proteins (21), a disparity that could also apply in vivo. With this in mind, it is curious to note that most studies reporting improved lung function with the use of fibrinolytic agents in ALI have focused predominantly on ventilationperfusion matching and oxygenation (2,16,50,57), with limited reporting on changes in lung mechanical function. The one study reporting a reduction in peak airway pressures following aerosolized tPA used a sheep model of burn and smoke inhalation injury (16), a model characterized by extensive obstruction of large and small airways with fibrinous debris (16).…”
Section: Discussionmentioning
confidence: 99%
“…An effect of nebulized heparin on systemic coagulation was reported in one study using a lung injury model (49), but not in studies using pulmonary infection models (36,49) or inhalation trauma models (38)(39)(40)(41)(42). None of these studies, however, showed systemic bleeding.…”
Section: Heparinmentioning
confidence: 98%
“…Nebulized heparin also affected various physiologic parameters and other outcomes, in particular during pulmonary infection (34,35), and inhalation trauma (38)(39)(40)(41)(42)). An effect of nebulized heparin on systemic coagulation was reported in one study using a lung injury model (49), but not in studies using pulmonary infection models (36,49) or inhalation trauma models (38)(39)(40)(41)(42).…”
Section: Heparinmentioning
confidence: 99%
See 1 more Smart Citation
“…These include antiadherence agents (blocking neutrophil adherence in the pulmonary microvasculature), leukotriene inhibitors, inhaled heparin, and antioxidants (42)(43)(44) , although controlled clinical studies are still necessary before these new treatment alternatives can be adopted in clinical practice.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%